Formação de professores e educação indígena: revisão da literatura - Almeida, Rainey Araújo de (Brasil, 2023)
Teacher training and indigenous education considers the constant struggles of communities, schools, teachers who strive for better conditions for an education focused on their specificities and differences. The objective of this monograph was to analyze the literature published in the format of scientific articles between 2017-2022 on the challenges of teacher training for indigenous school education. The work is about the interactive review of the literature that had a universe of 20 articles that were collected in the Portal Periódicos CAPES, and that were analyzed first via an integrative review protocol and after, submitted to the Content Analysis procedure. As a result, four categories were built, namely: 1) Teacher Training; 2) Mathematics Teaching; 3) Game in the transmission of traditional knowledge; 4) Indigenous School Education. The discussion turns to questions that the last two decades are marked by an intensification of indigenous schooling processes and the access of indigenous students to higher education becomes more evident, much as a result of the struggles that claim affirmative policies in the university context. There are indigenous people who are acting as teachers in the classroom, whether or not they speak the indigenous language of their people, but often, the indigenous language teacher who teaches does not have completed elementary school. And several teachers of indigenous school education are not indigenous and there are several reasons for this fact, but the most worrying is that if there were a requirement that the teacher of indigenous education be obligatorily indigenous, this would make the functioning of these schools unfeasible, since there are not, in no Brazilian state, there are enough indigenous teachers trained at a higher level to meet the entire demand for Basic Education teachers. As for the teaching of mathematics, the challenges are presented in such a way that if, in order to teach reading and writing, the teacher makes use of writing codes in literacy, and through this expands to the different forms of use of reading and writing, in mathematics the teacher will use the codes (numbers, lines, shapes, etc.). The difference in indigenous communities in this literacy and numeracy process is the use of ethnomathematics, that is, the cultural and traditional knowledge already acquired by children before entering school. Regarding games in the transmission of traditional knowledge, in Brazil, traditional games and games as they are found mostly originate from colonization, but there is also a great influence of indigenous culture. and finally, in relation to indigenous school education, it is understood that school education is a tool for indigenous societies to defend their rights before the constituted powers, in addition to being able to dialogue constructively with the different cultures that make up the Brazilian State. Finally, in the final considerations, fundamental points are presented, such as suggestions and recommendations for teacher training and quality indigenous education to truly achieve their autonomy.